2010
DOI: 10.1007/978-3-642-13025-0_58
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Development of Juvenile Delinquency by Simulation

Abstract: A large number of delinquent activities are performed by adolescents and only occur during this period in their lives. One of the main factors that influence this behaviour is social interaction, mainly with peers. This paper contributes a computational model that predicts delinquent behaviour during adolescence based on interaction with friends and classmates. Based on the model, which was validated based on empirical data, the level of delinquency of pupils is simulated over time. Furthermore, simulation exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…() and Bosse et al. () are also very interesting in that they relate to what we consider the main research gap. Most existing studies investigated the effects of class composition among children but not among adolescents.…”
Section: Effects Of Classroom Composition On Individual Behavioral Dementioning
confidence: 69%
See 3 more Smart Citations
“…() and Bosse et al. () are also very interesting in that they relate to what we consider the main research gap. Most existing studies investigated the effects of class composition among children but not among adolescents.…”
Section: Effects Of Classroom Composition On Individual Behavioral Dementioning
confidence: 69%
“…The few existing results concerning this issue are not conclusive. While a recent cross‐sectional study by Araos, Cea, Fernández, and Valenzuela () in Chile indicated that the level of marijuana use among the classmates was related to the individual rates of consumption among seventh graders, different results emerged from a study by Bosse, Gerritsen, and Klein (). Based on their data set of 194 seventh graders, these authors found little evidence of compositional effects but stressed the preliminary nature of their findings due to the small sample size and the incomplete information available on class composition.…”
Section: Effects Of Classroom Composition On Individual Behavioral Dementioning
confidence: 94%
See 2 more Smart Citations
“…However, there are also a few studies that did not find such classroom effects. For example, Henry et al (2000), in parts of their analyses, did not find evidence that classroom aggression affects individual aggressive behavior (see also e.g., Bosse, Gerritsen, & Klein, 2010). Other studies in research Area A did not predict individual social-emotional outcomes by the same characteristics of the classmates but used other classroom variables as predictors (e.g., Araos et al, 2014;Busching & Krahé, 2015;Henry et al, 2000;Hoglund & Leadbeater, 2004;Mercer et al, 2009;Stearns, Dodge, & Nicholson, 2008;Werthamer-Larsson, Kellam, & Wheeler, 1991).…”
Section: Main Effects Of Classroom Composition On Individual Social-ementioning
confidence: 94%